Study of Binding Efficiency of Tapioca Starch using Iornoxicam as a Model Drug - Kadoli, Poonam S (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In the following study starch obtained from the Tapioca is a starch extracted from the root of the plant species Manihot esculanta was used as a binder in different concentrations in Lornoxicam tablets. The tablets were formed by wet granulation method by using 2% w/v, 4% w/v, 6% w/v, 8% w/v and 10% w/v tapioca starch as binding agent. Formulated Lornoxicam tablets were further evaluated for various parameters i.e. weight variation, hardness, friability,drug content, disintegration time and in-vitro drug release. The starch obtained from Manihot esculanta was found to have a good binding property. The hardness and disintegration time of the tablets was found to be increased with increase in starch concentration. Tablets with highest binder concentration showed maximum hardness (7.96 kg/m2) and disintegration time (28.10min) and minimum friability (0.1%). After one hour tablets with 2% w/v starch showed maximum drug release (97.05%) and tablets with 10% w/v starch showed minimum drug release (79.98%).